Evaluation of Ghrelin Hormone, Erythrocyte Sedimentation Rate and C-Reactive Protein in Women Patients with Knee Osteoarthritis Thi-Qar Province / Iraq - Barzan, Maysm; Mohammed Ajah Aouda (University of Thi-Qar Journal of Science, 2025)
Degenerative joint disease usually results from articular cartilage deterioration and gradual loss. Degenerative joint disease usually results from articular cartilage deterioration and gradual loss. It is especially prevalent in older men and women. Primary and secondary osteoarthritis are the two types that can affect the knee. This study measured C-reactive protein, ghrelin hormone, and erythrocyte sedimentation rate in order to assess serum ghrelin in female patients with osteoarthritis in the knee. Samples of blood were taken from (48). Women with KOA were split into two age-based groups: twenty-four older patients (ages 51–70) and twenty-four other patients (ages 30–50). A control group of forty-eight healthy women was also included. Additionally, individuals were split into two age-based groups: (24) There are elderly women (ages 51–70) and others (ages 30–50) in this group. Findings: Compared to the control group, all patient groups with osteoarthritis in the knee had significantly higher levels of the hormone ghrelin, CRP, and ESR.